Spatial Audio - Jung-Woo Choi (Ed.); Woon Seng Gan (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This special issue compiles some of the latest state-of-the-art research works in the area of spatial audio and it serves as a good reference for both undergraduate and postgraduate students, and to researchers working in this exciting area of spatial audio.
English
Keywords: Novel Applications in Spatial Audio; Spatial Rendering and Sound Field Reproduction; Immersive audio for VR/AR; Binaural processing with Head Tracking Head related transfer function and their acquisition; Ambisonics and Wave field Synthesis; Binaural recording/Spatial sound capture and noise control; Sound Localization in spatial rendering; Assisted Listening; Signal Processing for headphones and loudspeakers; Loudspeakers and headphones for sound reproduction